Perlindungan Hukum Terhadap Muallaf Di Pematangsiantar Perspektif UU No. 39 Tahun 1999 Tentang Hak Asasi Manusia - Zainul Fuad; Muhammad Yadi Harahap; Abdul Majid Al Faruq (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
This study examines the legal protection of converts according to Law no. 39 of 1999 concerning Human Rights, to find out the implementation of Law no. 39 of 1999 concerning Human Rights Against Muallaf in Pematangsiantar, and To Review the Efforts of the Ministry of Law and Human Rights of North Sumatra in Legal Protection Against Muallaf in Pematangsiantar. This study uses a qualitative research method with a normative juridical approach; the data sources are primary and secondary data, the preliminary data are interviews, observations, and documentation. Then secondary data are references, doctrines, books on human rights, theses, studies by experts and scientists, laws for the protection of human rights, and all related literature. The results of this study are that respecting the rights of others is very important, even if it must be protected and enforced the law if there is something that harms people's rights, including the right to freedom of someone to embrace the religion they believe in. Here the government's role is vital in protecting one's rights. Violence against converts should not occur if the government cares and enforces the law according to the applicable law.